Perovskite gradient band gap film and preparation method and application thereof
The perovskite gradient bandgap film is prepared by layer-by-layer sequential deposition method, which solves the problems of film thickness control and bandgap regulation in the prior art, and realizes efficient and uniform perovskite film preparation, which improves the photoelectric conversion of photovoltaic devices efficiency.
Patent Information
- Application Number
- CN202410292858.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-03-14
AI Technical Summary
The existing wet preparation process cannot achieve the "laminated layer" preparation of gradient bandgap perovskite films, and the dry preparation process has not yet mature and efficient methods to solve the problems of film thickness control and bandgap regulation.
Perovskite gradient bandgap film was prepared by layer-by-layer sequential deposition method. The superposition structure of wide-bandgap and narrow-bandgap perovskite layers was used to regulate the thickness ratio, evaporation rate and current of lead halide and organic salts, and prepare a gradient bandgap with a gradient bandgap Multi-layer high-quality perovskite film.
A perovskite gradient bandgap film with high crystallinity and uniformity can match multiple scenario applications, improve the photoelectric conversion efficiency of photovoltaic devices, and flexibly regulate the bandgap to achieve the best ambient light utilization efficiency.
Smart Images

Figure CN119497550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a perovskite gradient bandgap film and a preparation method and application thereof. Background Art
[0002] Metal halide hybrid perovskite solar cells have the advantages of high power conversion efficiency and low cost, and are highly valued by academia and industry. At present, the wet process used to prepare perovskite thin films is only suitable for small-scale preparation (<100cm) on a laboratory scale. 2 ), the preparation of large-area components is limited. To achieve commercialization, a large-area preparation process suitable for industrial applications must be developed. Moreover, the solvents used in the wet process are harmful to the underlying functional layers and are also harmful to the environment.
[0003] In contrast, the use of dry preparation processes can avoid these shortcomings, and precursors of different materials can be uniformly deposited on the substrate. At the same time, during the vacuum evaporation process, the film thickness can be precisely controlled, which is suitable for industrial large-scale preparation. At present, the dry preparation process mainly includes three categories: co-evaporation, layer-by-layer sequential deposition, and gas / liquid assisted deposition. However, the gas / liquid assisted deposition method still has the shortcomings of large-area component preparation, and both co-evaporation and layer-by-layer sequential deposition have the potential to achieve large-area component preparation. However, there is currently no mature and efficient dry preparation process to solve the problems of limited film thickness control range in the wet preparation process and lack of uniformity in the preparation of perovskite layer band gap regulation by component screening.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a perovskite gradient bandgap film and a preparation method and application thereof, so as to solve the problem that the existing wet preparation process cannot realize the "layer-by-layer" preparation of the gradient bandgap perovskite film.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides a perovskite gradient bandgap film, which is formed by stacking at least one wide bandgap perovskite layer and at least one narrow bandgap perovskite layer;
[0008] The material of the wide bandgap perovskite layer is MA( 1-x1 )FA x1 Pb(I (1-y1-y2) Br y1 Cl y2)3, wherein: the range of x1 is 0≤x1≤1; the range of y1 is 0≤y1≤1; the range of y2 is 0≤y2≤1; y1 and y2 are not 0 at the same time; the range of the bandgap width Eg1 of the wide bandgap perovskite layer is 1.6eV<Eg1≤2.3eV;
[0009] The material of the narrow bandgap perovskite layer is MA( 1-x2 )FA x2 Pb z Sn (1-z) PbI3, wherein: the range of x2 is 0≤x2≤1; the range of Z is 0≤z≤1; the range of the bandgap width Eg2 of the narrow bandgap perovskite layer is 1.35eV<Eg2≤1.6eV.
[0010] Specifically, the number of layers of the wide bandgap perovskite layer and the narrow bandgap perovskite layer are both integers within the range of 1-5.
[0011] Specifically, the band gap width of the perovskite gradient band gap film ranges from 1.35 eV to 2.3 eV.
[0012] Furthermore, the wide bandgap perovskite layer can be prepared by evaporating lead halide A1 and organic salt A2 respectively, and then annealing at 60-150° C. for 10-30 minutes. The thickness of the lead halide A1 is 10-100 nm; the thickness ratio of the lead halide A1 to the organic salt A2 is 1:(1-2.5).
[0013] Specifically, the lead halide A1 is at least one of PbI2, PbBr2, and PbCl2; the organic salt A2 is at least one of FAI, FABr, FACl, MAI, MABr, and MACl.
[0014] Furthermore, the narrow bandgap perovskite layer can be prepared by evaporating lead halide B1 and organic salt B2 respectively, and then annealing at a temperature of 60 to 150° C. for 10 to 30 minutes. The thickness of the lead halide B1 is 10 to 100 nm; the thickness ratio of the lead halide B1 to the organic salt B2 is 1: (1 to 2.5).
[0015] Specifically, the lead halide B1 is at least one of PbI2 and SnI2; the organic salt B2 is at least one of FAI and MAI.
[0016] Furthermore, the evaporation current of the lead halide A1 and the lead halide B1 is independently 1.8 to 2.0 A; the evaporation rate is independently
[0017] Furthermore, the evaporation current of the organic salt A2 and the organic salt B2 are independently 0.8 to 1.0 A; the evaporation rate is independently
[0018] On the other hand, the present invention provides a method for preparing a perovskite gradient bandgap film, which is prepared by stacking at least one wide bandgap perovskite layer and at least one narrow bandgap perovskite layer, and then annealing at a temperature of 60 to 150°C for 10 to 30 minutes; wherein all narrow bandgap perovskite layers are located above all wide bandgap perovskite layers.
[0019] On the other hand, the present invention also provides the use of the above-mentioned perovskite gradient bandgap film in perovskite solar cells.
[0020] In addition, the present invention also provides a perovskite solar cell based on the above-mentioned perovskite gradient bandgap film, specifically:
[0021] The perovskite solar cell is a positive structure (nip type), and includes a transparent conductive substrate, an electron transport layer (ETL), a perovskite gradient bandgap film, a hole transport layer (HTL), and a metal electrode stacked in sequence from bottom to top; the perovskite gradient bandgap film is formed by stacking a plurality of wide-bandgap perovskite layers and a plurality of narrow-bandgap perovskite layers.
[0022] Alternatively, the perovskite solar cell is an inverted structure (pin type), and includes a transparent conductive substrate, a hole transport layer (HTL), a perovskite gradient bandgap film, an electron transport layer (ETL), and a metal electrode stacked in sequence from bottom to top; the perovskite gradient bandgap film is formed by stacking a plurality of wide-bandgap perovskite layers and a plurality of narrow-bandgap perovskite layers.
[0023] The present invention has no particular restrictions on the transparent conductive substrate of the perovskite solar cell, and any conductive substrate known in the art can be used as long as the purpose of the present invention can be achieved. For example, the transparent conductive substrate may include a flexible conductive substrate or a rigid conductive substrate; wherein the flexible conductive substrate may be a fluorine-doped tin oxide (FTO) flexible conductive substrate or an indium-doped tin oxide (ITO) flexible conductive substrate; and the rigid conductive substrate may be a FTO conductive glass substrate or an ITO conductive glass substrate.
[0024] The present invention has no particular restrictions on the materials of the electron transport layer of the perovskite solar cell, which can be materials or combinations thereof known to those skilled in the art, such as titanium dioxide (TiO2) electron transport layer, tin dioxide (SnO2) electron transport layer, fullerene electron transport layer, C60 electron transport layer or zinc oxide (ZnO) electron transport layer, etc.; and the present invention has no particular restrictions on the thickness of the electron transport layer, as long as the purpose of the present invention can be achieved, for example, the thickness of the electron transport layer can be 20 to 100 nm. The present application has no particular restrictions on the preparation process of the electron transport layer, for example, solution spin coating, solution scraping, solution spraying, slit coating or hydrothermal growth can be used. In some embodiments of the present application, the preparation method of the electron transport layer is slit coating.
[0025] The present invention has no particular restriction on the hole transport layer of the perovskite solar cell, which can be a material or a combination thereof known to those skilled in the art, for example, it can be any one of the layered structures prepared by nickel oxide, doped nickel oxide, cuprous iodide, cuprous thiocyanate, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), PEDOT:PSS or Spiro-OMeTAD; and the present invention has no particular restriction on the thickness of the hole transport layer, as long as the purpose of the present invention can be achieved, for example, it can be 10nm to 100nm; and the present invention has no particular restriction on the preparation process of the hole transport layer, for example, solution spin coating, solution scraping, slit coating or vapor phase method can be used. In some embodiments of the present invention, the preparation method of the hole transport layer is slit coating.
[0026] The present invention has no particular restrictions on the material of the metal electrode of the perovskite solar cell, which can be a material or a combination thereof known to those skilled in the art, such as a gold (Au) electrode, a silver (Ag) electrode, an aluminum (Al) electrode, or a copper (Cu) electrode. In addition, the present invention has no particular restrictions on the thickness of the metal electrode, as long as the purpose of the present invention can be achieved, for example, it can be 50 to 100 nm, and the electrode thickness within this range can achieve better results. Of course, those skilled in the art can select a suitable electrode thickness as needed, and the present invention has no particular restrictions on the preparation process of the metal electrode, for example, a thermal evaporation method can be used.
[0027] In addition, it should be noted that, as needed, the perovskite solar cell provided by the present invention can also include other layers. For example, in order to reduce the electron state density, a passivation layer can be set in the perovskite layer and the hole transport layer, and the material of the passivation layer can be phenylpropylammonium iodide (PPAI).
[0028] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0029] (1) The perovskite gradient bandgap film prepared by the layer-by-layer sequential deposition method has high crystallinity and good uniformity. By precisely controlling the thickness ratio of the evaporated lead halide and organic salt, the evaporation rate and evaporation current of the lead halide and organic salt, a multi-layer high-quality perovskite film stacking structure with a gradient bandgap is prepared; and based on the energy level control and optimization matching charge transfer layer structure, the high-efficiency preparation of multi-layer perovskite photovoltaic devices with a gradient bandgap is achieved.
[0030] (2) The present invention prepares perovskite gradient bandgap films with different bandgap ranges by stacking a wide bandgap perovskite layer and a narrow bandgap perovskite layer, so that the bandgap range is 1.35eV to 2.3eV, thereby matching multiple scene applications; and according to the spectral variation range of the light source, the stacked structure of the perovskite polycrystalline film with matching bandgap is flexibly adjusted to achieve the optimal ambient light utilization efficiency and realize efficient utilization of the spectrum in different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0033] Figure 1 Schematic diagram of a perovskite solar cell with an upright structure (nip type);
[0034] Figure 2 Schematic diagram of an inverted structure (pin type) perovskite solar cell;
[0035] Figure 3 The electron microscope images of the first narrow bandgap perovskite layer prepared in Examples 1 to 5 (scale is 10 μm);
[0036] Figure 4 The electron microscope images of the first narrow bandgap perovskite layer prepared in Example 1 and Comparative Examples 1 to 3 (scale is 10 μm);
[0037] Figure 5 The current density-voltage curves of the perovskite solar cells prepared in Examples 1 to 5 under standard sunlight;
[0038] Figure 6 The current density-voltage curves of the perovskite solar cells prepared in Example 1 and Comparative Examples 1 to 3 under standard sunlight. DETAILED DESCRIPTION
[0039] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0041] Example 1
[0042] This embodiment provides a method for preparing a pin-type perovskite solar cell, which is as follows:
[0043] <Preparation of Transparent Conductive Substrate>
[0044] The ITO conductive glass substrate was cleaned with ITO cleaning agent, water and ethanol in sequence for 15 minutes, treated with UV-ozone cleaner for 15 minutes, transferred to the clean bench and dried under infrared drying lamp for later use.
[0045] <Preparation of hole transport layer>
[0046] First, prepare 1.5 mg mL -1 The chlorobenzene solution of F4-TCNQ was stirred at 70 °C for 15 min and 1.5 mg mL -1 After PTAA is dissolved, add 1% mass fraction of F4-TCNQ chlorobenzene solution to the PTAA chlorobenzene solution and stir at room temperature for 4 hours. Then take 70uL of the prepared PTAA solution and drop it on the ITO conductive glass substrate treated with UV-ozone, spin-coat at 6000rpm for 30s, and then anneal at 100℃ for 10min to complete the preparation of the hole transport layer.
[0047] <Preparation of perovskite gradient bandgap films>
[0048] ①Preparation of the first wide bandgap perovskite layer:
[0049] First, a thin layer of PbBr2 was evaporated on the hole transport layer (the evaporation current of PbBr2 was 1.8A and the evaporation rate was ), with a thickness of 50nm; and then single-source evaporation of FACl (the evaporation current of FACl is 0.8A, and the evaporation rate is ), with a thickness of 100 nm; and then annealing at 100° C. for 20 min to obtain a first wide bandgap perovskite layer;
[0050] ②Preparation of the first narrow bandgap perovskite layer:
[0051] A thin layer of a mixture of PbI2 and SnI2 was first evaporated on the first wide bandgap perovskite layer (the mass ratio of the mixture of PbI2 and SnI2 was 9:1, the evaporation current of the mixture of PbI2 and SnI2 was 2.0 A, and the evaporation rate was ), with a thickness of 100 nm; and then single-source evaporation FAI (the evaporation current of FAI is 1.0 A, and the evaporation rate is ), with a thickness of 160 nm; and then annealing at 100° C. for 20 min to obtain the first narrow bandgap perovskite layer, thereby completing the preparation of the perovskite gradient bandgap film.
[0052] Among them, the thickness ratio of PbBr2 and FACl in the first wide band gap perovskite layer is 1:2; the thickness of the mixture of PbI2 and SnI2 and FAI in the first narrow band gap perovskite layer is 1:1.6.
[0053] <Preparation of Electron Transport Layer and Metal Electrode>
[0054] At air pressure <4.5×10 -4 In the case of Pa, C 60 (thickness of 40nm), BCP (thickness of 6nm) and Ag (thickness of 120nm) are used to complete the preparation of pin-type perovskite solar cells.
[0055] Example 2
[0056] This embodiment provides a method for preparing a nip-type perovskite solar cell, which is as follows:
[0057] <Preparation of Transparent Conductive Substrate>
[0058] The ITO conductive glass substrate was cleaned with ITO cleaning agent, water and ethanol in sequence for 15 minutes, treated with UV-ozone cleaner for 15 minutes, transferred to the clean bench and dried under infrared drying lamp for use.
[0059] <Preparation of Electron Transport Layer>
[0060] On an ITO conductive glass substrate, a 20nm SnO2 buffer layer was prepared by radio frequency sputtering of SnO2 target using an atomic layer deposition (ALD) system.
[0061] <Preparation of perovskite gradient bandgap films>
[0062] ① Preparation of the first wide bandgap perovskite layer:
[0063] First, a thin layer of a mixture of PbBr2 and PbI2 was evaporated on the electron transport layer (the mass ratio of PbBr2 and PbI2 was 20:1, the evaporation current range of the mixture of PbBr2 and PbI2 was 1.8A, and the evaporation rate was ), with a thickness of 100 nm; and then single-source evaporation of FABr (the evaporation current of FABr is 0.8 A, and the evaporation rate is ), with a thickness of 100 nm; and then annealing at 150° C. for 15 min to obtain a first wide bandgap perovskite layer;
[0064] ②Preparation of the first narrow bandgap perovskite layer:
[0065] First, a thin layer of PbI2 was evaporated on the first wide bandgap perovskite layer (the evaporation current of PbI2 was 2.0A and the evaporation rate was ), with a thickness of 100 nm; and then single-source evaporation FAI (the evaporation current of FAI is 1.0 A, and the evaporation rate is ), with a thickness of 100 nm; and then annealing at 150°C for 15 min to obtain the first narrow bandgap perovskite layer.
[0066] Among them, the thickness ratio of the mixture of PbBr2 and PbI2 to FABr in the first wide band gap perovskite layer is 1:1; the thickness ratio of PbI2 to FAI in the first narrow band gap perovskite layer is 1:1.
[0067] <Preparation of hole transport layer>
[0068] ALD deposition is used to deposit NiO on the surface of the perovskite gradient bandgap film by radio frequency sputtering. x Target material, sputtering power is 90W at 0.3Pa argon and room temperature, sputtering for 10min, depositing 30nm NiO x Hole transport layer. In order to clean the target material, the target material was sputtered for 4 minutes before the formal deposition.
[0069] <Preparation of Metal Electrode>
[0070] At air pressure <4.5×10 -4 In the case of Pa, Au electrode (thickness of 120 nm) was evaporated to complete the preparation of nip-type perovskite solar cell.
[0071] Example 3
[0072] On the basis of Example 1, the difference from Example 1 is: <Preparation of perovskite gradient bandgap film>, specifically as follows:
[0073] ①Preparation of the first wide bandgap perovskite layer:
[0074] First, a thin layer of PbBr2 was evaporated on the hole transport layer (the evaporation current of PbBr2 was 1.8A and the evaporation rate was ), with a thickness of 50nm; then evaporate a mixture layer of FABr and FACl (the mass ratio of FABr and FACl is 30:1, the evaporation current of the mixture of FABr and FACl is 0.8A, and the evaporation rate is ), with a thickness of 100 nm; and then annealed at 60°C for 30 min;
[0075] ②Prepare the first narrow bandgap perovskite layer on top of the first wide bandgap perovskite layer:
[0076] A thin layer of PbI2 was evaporated on the first wide bandgap perovskite layer (the evaporation current of PbI2 was 2.0 A and the evaporation rate was ), with a thickness of 100 nm; and then single-source evaporation FAI (the evaporation current of FAI is 1.0 A, and the evaporation rate is ), with a thickness of 250 nm; and then annealing at 60°C for 30 min, thereby completing the preparation of the perovskite gradient band gap film.
[0077] Among them, the thickness ratio of PbI2 and FAI in the first narrow bandgap perovskite layer is 1:2.5, and the thickness ratio of PbBr2 to the mixture of FABr and FACl in the first wide bandgap perovskite layer is 1:2.
[0078] Example 4
[0079] On the basis of Example 1, the difference from Example 1 is that the preparation of the first narrow bandgap perovskite layer in the preparation process of the perovskite gradient bandgap film is as follows:
[0080] First, a mixture layer of PbI2 and PbCl2 was evaporated (the mass ratio of PbI2 and PbCl2 was 50:1, the evaporation current of the mixture of PbI2 and PbCl2 was 2.0A, and the evaporation rate was ), with a thickness of 100 nm; and then FAI was evaporated (the evaporation current of FAI was 1.0 A and the evaporation rate was ), with a thickness of 160 nm; and then annealing at 150°C for 10 min to obtain the first narrow bandgap perovskite layer.
[0081] Among them, the thickness ratio of the mixture layer of PbI2 and PbCl2 and FAI in the first narrow bandgap perovskite layer is 1:1.6.
[0082] Example 5
[0083] On the basis of Example 1, the difference from Example 1 is that: in <Preparation of perovskite gradient bandgap film>, the narrow bandgap perovskite layer includes a first narrow bandgap perovskite layer and a second narrow bandgap perovskite layer; the wide bandgap perovskite layer includes a first wide bandgap perovskite layer and a second wide bandgap perovskite layer, and the specific preparation process is as follows:
[0084] ①Prepare the first wide bandgap perovskite layer: first evaporate a thin layer of PbBr2 (evaporation current is 1.8A, evaporation rate is ), with a thickness of 50 nm, and then single-source evaporation of FACl (evaporation current of 0.8 A, evaporation rate of )Prepare the first wide bandgap perovskite layer with a thickness of 100nm.
[0085] ②Prepare the second wide bandgap perovskite layer: first evaporate a thin layer of a mixture of PbBr2 and PbI2 (the mass ratio of PbBr2 and PbI2 is 50:1, the evaporation current of the mixture of PbBr2 and PbI2 is 1.8A, and the evaporation rate is ), with a thickness of 50 nm, and then FABr was deposited by single-source evaporation (the evaporation current was 0.8 A and the evaporation rate was )Prepare a second wide bandgap perovskite layer with a thickness of 100 nm.
[0086] ③Prepare the first narrow bandgap perovskite layer: first evaporate a mixture layer of PbI2 and SnI2 (the mass ratio of PbI2 and SnI2 is 9:1, the evaporation current of the mixture of PbI2 and SnI2 is 2.0A, and the evaporation rate is ), with a thickness of 100 nm; then the FAI layer was evaporated (the evaporation current was 1.0 A, and the evaporation rate was ), with a thickness of 160nm.
[0087] ④Prepare the second narrow bandgap perovskite layer: first evaporate a mixture layer of PbI2 and SnI2 (the mass ratio of PbI2 and SnI2 is 8:2, the evaporation current of the mixture of PbI2 and SnI2 is 2.0A, and the evaporation rate is ), with a thickness of 100 nm; then the FAI layer was evaporated (the evaporation current was 1.0 A, and the evaporation rate was ), with a thickness of 160nm.
[0088] Comparative Example 1
[0089] In <Preparation of Perovskite Gradient Bandgap Film>, regarding the preparation of the first narrow bandgap perovskite layer, the thickness of the PbI2 evaporated is 100nm, the thickness of the FAI evaporated is 80nm, and the thickness ratio of PbI2 and FAI is 5:4; the rest is the same as Example 1.
[0090] Comparative Example 2
[0091] In <Preparation of Perovskite Gradient Bandgap Film>, regarding the preparation of the first narrow bandgap perovskite layer, the thickness of the PbI2 vapor deposition is 100nm, and the thickness of the FAI vapor deposition is 300nm, wherein the thickness ratio of PbI2 and FAI is 1:3; the rest is the same as Example 1.
[0092] Comparative Example 3
[0093] In the preparation of the first narrow bandgap perovskite layer, the evaporation current of PbI2 is 2.0A and the evaporation rate is The rest is the same as Example 1.
[0094] The verification process of narrow bandgap perovskite films is as follows:
[0095] ① The narrow bandgap perovskite films prepared in Examples 1 to 5 were observed under a scanning electron microscope (SEM), and the corresponding SEM morphology images were obtained, see Figure 3 As shown; the narrow bandgap perovskite film prepared in Example 1 and the narrow bandgap perovskite films prepared in Comparative Examples 1 to 3 were observed under a scanning electron microscope (SEM), and the corresponding SEM morphology images were obtained, see Figure 4 shown.
[0096] ② Draw the JV characteristic curves of the corresponding perovskite cells in Examples 1 to 5 (see Figure 5 ), JV characteristic curves of the corresponding perovskite cells in Example 1 and Comparative Examples 1 to 3 (see Figure 6 ).
[0097] Depend on Figure 3 It can be seen that Examples 1 to 5 can all produce uniform and dense high-quality perovskite films. Figure 5 It can be seen that Examples 1-5 can achieve the preparation of high-quality devices above 19%, and with the increase of perovskite grains, the highest efficiency of dry evaporation can exceed 23%. This shows that the present invention provides a preparation process for high-efficiency devices.
[0098] Depend on Figure 4 It can be seen that the surface morphology of the perovskite films prepared in Comparative Examples 1 to 3 is significantly worse, with more holes, incomplete coverage and a rougher morphology. By comparing Comparative Examples 1 to 3 with Example 1, and combining Figure 6It can be seen from the curves and related data that the photoelectric conversion efficiency of the perovskite gradient bandgap film in Example 1 is 23.26%, and the photoelectric conversion efficiencies of the perovskite gradient bandgap films in Comparative Examples 1, 2 and 3 are 10.68%, 13.71% and 17.08%, respectively. That is, the photoelectric conversion efficiency of the perovskite gradient bandgap film in Example 1 of the present invention is significantly better than that of Comparative Examples 1 to 3. Moreover, the photoelectric performance (open circuit voltage VOC, short circuit current density JSC, filling factor FF) of the device based on the perovskite gradient bandgap film prepared in Example 1 is much better than that of the device based on the perovskite gradient bandgap film prepared in Comparative Examples 1 to 3. It can be seen that the thickness ratio of the lead halide (B1, A1) and the organic salt (B2, A2) needs to be controlled within the range of 1: (1 to 2.5) and the evaporation rate of the lead halide is controlled within the range of 1: (1 to 2.5). range, can ensure that devices based on perovskite gradient band gap films have good optoelectronic properties.
[0099] It should be noted that the thickness ratio of the lead halide and the organic salt and the evaporation rate and other parameters in the present invention have similar influence trends on the wide bandgap perovskite layer and the narrow bandgap perovskite layer, and the only difference is the range of the bandgap width. Specifically, the bandgap width Eg2 of the narrow bandgap perovskite layer is in the range of 1.35eV<Eg2≤1.6eV; the bandgap width Eg1 of the wide bandgap perovskite layer is in the range of 1.6eV<Eg1≤2.3eV. Therefore, the above verification process is only discussed around the narrow bandgap perovskite film, and the verification of the wide bandgap perovskite film is not repeated here.
[0100] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0101] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A perovskite gradient band gap film, characterized in that: The method is formed by stacking at least one wide band gap perovskite layer and at least one narrow band gap perovskite layer; The material of the wide bandgap perovskite layer is MA (1-x1) FA x1 Pb(I (1-y1-y2) Br y1 Cl y2 )3, wherein: the range of x1 is 0≤x1≤1; the range of y1 is 0≤y1≤1; the range of y2 is 0≤y2≤1; y1 and y2 are not 0 at the same time; the range of the bandgap width Eg1 of the wide bandgap perovskite layer is 1.6eV<Eg1≤2.3eV; The material of the narrow bandgap perovskite layer is MA (1-x2) FA x2 Pb z Sn (1-z) PbI3, wherein: the range of x2 is 0≤x2≤1; the range of Z is 0≤z≤1; the range of the bandgap width Eg2 of the narrow bandgap perovskite layer is 1.35eV<Eg2≤1.6eV.
2. The perovskite gradient band gap film according to claim 1, characterized in that: The number of layers of the wide bandgap perovskite layer and the narrow bandgap perovskite layer are both integers within a range of 1 to 5.
3. The perovskite gradient band gap film according to claim 1, characterized in that: The wide bandgap perovskite layer is prepared by evaporating lead halide A1 and organic salt A2 respectively, and then annealing; the narrow bandgap perovskite layer is prepared by evaporating lead halide B1 and organic salt B2 respectively, and then annealing.
4. The perovskite gradient band gap film according to claim 3, characterized in that: The process parameters of the annealing treatment of the wide bandgap perovskite layer and the narrow bandgap perovskite layer are the same, specifically: the annealing temperature is 60 to 150° C., and the annealing time is 10 to 30 minutes.
5. The perovskite gradient band gap film according to claim 3, characterized in that: The thickness ratio of the lead halide A1 and the organic salt A2 of the wide bandgap perovskite layer is 1:(1-2.5); the thickness ratio of the lead halide B1 and the organic salt B2 of the narrow bandgap perovskite layer is 1:(1-2.5).
6. The perovskite gradient band gap film according to claim 3, characterized in that: The lead halide A1 is at least one of PbI2, PbBr2, and PbCl2; the organic salt A2 is at least one of FAI, FABr, FACl, MAI, MABr, and MACl.
7. The perovskite gradient band gap film according to claim 3, characterized in that: The lead halide B1 is at least one of PbI2 and SnI2; the organic salt B2 is at least one of FAI and MAI.
8. The perovskite gradient band gap film according to claim 3, characterized in that: The evaporation current of the lead halide B1 and the lead halide A1 are both 1.8-2.0A, and the evaporation rate is The evaporation current of the organic salt B2 and the organic salt A2 are both 0.8-1.0A, and the evaporation rate is 9. A method for preparing a perovskite gradient band gap film according to any one of claims 1 to 8, characterized in that: The method is prepared by stacking at least one wide band gap perovskite layer and at least one narrow band gap perovskite layer, and then annealing at a temperature of 60 to 150° C. for 10 to 30 minutes.
10. An application of the perovskite gradient band gap film according to any one of claims 1 to 8 in a perovskite solar cell, characterized in that: The perovskite solar cell has a positive structure or an inverted structure.
Citation Information
Patent Citations
Inverted perovskite solar cell and preparation method thereof
CN116801645A
Perovskite battery of gradual change band gap
CN207320169U